Federal Constitution of Malaysia and unity: an analysis from several perspectives - Mokhtar, Khairil Azmin (2011)

(untitled)
Unity in Malaysia faces at least 2 main challenges, namely, unity of territory and unity of community. To overcome these challenges, the fundamental and supreme law of the country is equipped with several mechanisms and institutions. Some aspects of the solutions provided for by the Constitution are found in most countries are in compliance with general democratic norms. However, some solutions appear to depart from the generally practiced norms or are rather the exceptional and salient features of the Malaysian Constitution. This paper seeks to highlight certain aspects of the constitution which have vital roles in promoting and ensuring unity of the nation and to show that the intriguing features of the Constitution are significant in maintaining peaceful co-existence between the diverse communities in the country.